Community pharmacy in Lebanon: A societal perspective - Iskandar K; Hallit S; Bou Raad E; Droubi F; Layoun N; Salameh P. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Objective: To assess patients' attitudes towards the community pharmacist's role and determine their negative and positive reactions towards community pharmacists in Lebanon. Methods: A cross-sectional study, conducted between January and April 2016, was designed to assess the general public satisfaction with the services provided by the community pharmacies. It was carried out, using a proportionate random sampling of Lebanese community pharmacies from each district. Two sided statistical tests were used to compare between group percentages, Wilcoxon test for quantitative variables with non-homogeneous variances or non-normal distribution, and Student's t-test for quantitative variables of normal distribution and homogeneous variances. The ANOVA test was used to compare between three groups or more, and Pearson correlation coefficient were used to correlate between quantitative variables. Results: a total of 565 participants completely answered the survey questions with a response rate of 94%. The bivariate analysis showed that the patient perception index was positively and significantly correlated with the patient level of expectation index, the overall pharmacy experience and the patient's reason for visiting the pharmacy (p<0.001 for all 3 variables) but was negatively correlated with the barriers for asking questions significantly (p=0.032). On the other hand, this perception index was significantly and positively associated with the number of pharmacy visits, the age categories, the level of education and the family monthly income (p<0.05 for all variables). Conclusion: Public perception and attitude toward community pharmacist in Lebanon is poor despite highly qualified pharmacists. Aspects of pharmacy services most relevant to patients were respect, empathy, a friendly staff, listening carefully, giving quality time, responding quickly to their needs and respecting their privacy. The ministry of Health in Lebanon, along with the Lebanese Order of Pharmacists should educate the pharmacist about working on the different issues patients are complaining about in order to play a more important role in the society and become the number one trusted health care professional.